Effective Communication and Knowledge Level of Health Workers in an Effort to Reduce Stunting Rates in Probolinggo Regency - Sunanto (Poltekkes Kemenkes Tasikmalaya, 2026)
The phenomenon of stunting in Probolinggo Regency is something very serious to be handled, this is caused by the condition of malnutrition that occurs in children in Probolinggo Regency so that what causes children to be short compared to their age, many factors can cause stunting including socioeconomic conditions, maternal nutrition during pregnancy, pain in babies, and lack of nutritional intake in infants. This study aims to analyze the relationship between Effective Communication and Knowledge of Health Workers in an effort to reduce stunting rates in Probolinggo Regency. This type of study is quantitative with a correlational analytical study design with a cross sectional approach. The population used was all Nurses, Midwives and Nutritionists with a total of 2700 respondents and the sample used was 348 using the Proportional sampling technique. Analysis Test Using Spearmen Rank with SPPSS 25 results with a cross-tabulation value between Effective Communication and the level of knowledge with a reduction in the Stunting rate adjusted to a Sig value of 0.000, this can be interpreted that effective communication has a strong impact on the success of reducing the Stunting rate in Probolinggo Regency. Health workers are the driving force in efforts to reduce stunting rates Therefore, preventing stunting, efforts to reduce stunting rates with effective communication strategies, increasing knowledge of health workers are needed to create a personal approach and trust between health workers and the community so that changes in people's behavior for the better can occur so that they can reduce stunting incidence in the district Probolinggo.